THE DIVERSITY AND ACTIVITY OF SUBTERRANEAN TERMITES IN THE RESIDENTIAL AREA OF BOGOR, WEST JAVA, INDONESIA - Arinana, Arinana; Permana, Rian; Rahmawati, Anindya Intan; Andika, Riki (Indonesian Journal of Forestry Research, 2025)
The housing demands in Bogor City have been on the rise, leading to environmental changes affecting pest organisms, especially subterranean termites. This research aimed to identify various species of subterranean termites in Bogor City, analyze soil and weather conditions, and evaluate termite attack frequency and severity. The study spanned 12 designated sub-districts. In each area, 25 bait wood (2 x 2 x 46 cm) crafted from pine wood and treated with water vapor pressure (105°C, 1 bar, 5 hours) were installed. Soil samples were gathered from each sampled village, while weather data was specifically documented in one sub-district. Findings uncovered three termite species inhabiting residential zones of Bogor City: Microtermes insperatus, Macrotermes gilvus, and Schedorhinotermes javanicus, with Microtermes insperatus emerging as the predominant species. The soil and weather conditions significantly favored termite existence in Bogor City. Termite attack prevalence stood at 38%, and the degree of wood damage ranged from 4 to 9.